Changes in Cardiomyocyte Cell Cycle and Hypertrophic Growth During Fetal to Adult in Mammals - Sanford P. Bishop; Yang Zhou; Yuji Nakada; Jianyi Zhang (2021)
The failure of adult cardiomyocytes to reproduce themselves to repair an injury results in the development of severe cardiac disability leading to death in many cases. The quest for an understanding of the inability of cardiac myocytes to repair an injury has been ongoing for decades with the identification of various factors which have a temporary effect on cell-cycle activity. Fetal cardiac myocytes are continuously replicating until the time that the developing fetus reaches a stage of maturity sufficient for postnatal life around the time of birth. Recent reports of the ability for early neonatal mice and pigs to completely repair after the severe injury has stimulated further study of the regulators of the cardiomyocyte cell cycle to promote replication for the remuscularization of injured heart. In all mammals just before or after birth, single-nucleated hyperplastically growing cardiomyocytes, 1X2N, undergo ≥1 additional DNA replications not followed by cytokinesis, resulting in cells with ≥2 nuclei or as in primates, multiple DNA replications (polyploidy) of 1 nucleus, 2X2(+)N or 1X4(+)N. All further growth of the heart is attributable to hypertrophy of cardiomyocytes. Animal studies ranging from zebrafish with 100% 1X2N cells in the adult to some strains of mice with up to 98% 2X2N cells in the adult and other species with variable ratios of 1X2N and 2X2N cells are reviewed relative to the time of conversion. Various structural, physiologic, metabolic, genetic, hormonal, oxygenation, and other factors that play a key role in the inability of post-neonatal and adult myocytes to undergo additional cytokinesis are also reviewed.